If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4x = 6x Combine like terms: 2x + 4x = 6x 6x = 6x Add '-6x' to each side of the equation. 6x + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| x^2+6x-55= | | 7.2k-4.5-1.3k=20.5-6.6k | | 9x+7=-2 | | 4x+11=x-7 | | 25y^2-x^2= | | 4x^2+34x=0 | | 4n+1=14 | | 3x-18=2x | | 2-8y=-14 | | 3(x-2)-(7x+2)=4(3x+1) | | -2x^2+12x-16=0 | | 2u^4x^4-30u^9x^3y^2= | | 4x^2+8x=-3 | | x-10=23 | | 21.6-d=5d | | 12x-3=90 | | 5m+18=8m-3 | | 4n+6-2n=-2n+3 | | 9-(4(7)-8)=x | | 3n+7=11 | | 9-(4(7)-8)= | | n+3=11-3 | | 9+3x=7-2x | | 4n+6-2n=2n+3 | | 5m+18=m-3 | | 7x+6=90 | | y^4-10y^2+y^4=0 | | -3-11=8x+16-7x | | (x+2)(4x-9)=(2x+3)(3x-10) | | x(7x+2)=8 | | (x-4)2=x-5 | | (3x-1)(x+2)=(5x+1)(x-2) |